Ethnobotanical study on plant resources from sacred groves of Dakshin Dinajpur district, West Bengal, India - Sarkar, Kushankur; Roy, Priyankar; Panda, Subhasis; Choudhuri, Chandrani; Chowdhury, Monoranjan (Ethnobotany Research and Applications, 2023)
Background: Sacred groves found in Dakshin Dinajpur district are natural in-situ conservatories that provide a home to numerous biological entities with rich ethnomedicinal plant diversity. Native communities have been conserving these groves through their own beliefs and folklore practices and they possess vast knowledge of herbal ethnic medicines. The current study aims to explore the ethnic traditional practices of medicinally important plants among different indigenous communities residing in sacred grove-centric villages throughout the district. Methods: For the current study, 15 ethnomedicinally enriched sacred groves were selected. Ethnomedicinal data were collected from 179 informants and were quantitatively analyzed using various statistical indices viz., Use value, Informant consensus factor, Fidelity level, and Relative Frequency of citation. With the help of an in-silico network pharmacological study, the findings were revalidated. Results: In the present study, a total of 105 ethnic plants belonging to 93 genera and 47 families were documented and the most dominant plant family was Fabaceae. The diseases reported by the informants were classified into 16 different disease clusters. Cuscuta reflexa Roxb., Heliotropium indicum L. and Cynodon dactylon (L.) Pers. were the most popular medicinal plants. Conclusion: Gathering such first-hand information about ancient traditional practices will be helpful in further pharmacological studies and may show new paths to modern therapeutic approaches. Keywords: Sacred Groves; Traditional Knowledge; Dakshin Dinajpur; Quantitative analysis; in-silico